A finite element investigation on design parameters of bare and polymer-covered self-expanding wire braided stents. (March 2021) - McKenna, Ciara G.; Vaughan, Ted J.
Abstract: Self-expanding covered braided stents are routinely used across a diverse range of clinical applications, but few computational studies have attempted to replicate their complex behaviour. In this study, a computational framework was developed to predict the functional performance of bare and covered self-expanding wire braided stents, with a systematic evaluation on the effect of various braid and cover parameters presented. Simulated radial force and kink deformation tests show good agreement to experimental data for covered braided stents across a range of braid angles and cover thicknesses. Our results demonstrate that braid angle is a key governing parameter that dictates the radial and kink performance of both bare-metal and covered wire braided stents. It was also demonstrated that addition of a polymeric cover to a wire braided stent causes a stiffer radial response across all braid angles, particularly when thicker and/or stiffer covering systems were considered. This study represents the first experimentally-validated computational model for covered wire braided stent systems and has excellent potential to be used in future design of these devices for a range of applications.